Edukasi Kesehatan Melalui Pelatihan Pembuatan Sabun dan Handsanitizer Ramah Lingkungan di Desa Subo Kabupaten Jember - Eryani, Mikhania Christiningtyas; Hidayah, Amaliyah Nurul (Jurnal Pengabdian UNDIKMA, 2023)
This service activity aims to increase the knowledge and skill of young women in Subo Village in making soap and hand sanitizer made from natural, environmentally friendly materials. The method used in this activity was the method of counseling and product manufacturing training. The instrument for evaluating this service was a questionnaire, which was analyzed descriptively, qualitatively, and quantitatively. The results of this service showed that the participant's knowledge and skills increased. The data evidence this: the participant's score was 80.7 before and after the service was 86. So that the increase in the participant's score after the service was carried out was 5.3 or 6.6%. This increase occurred in aspects of the chemical content of klerak and the method of making soap and hand sanitizer.